Blood nickel level and its toxic effect after transcatheter closure of persistent duct arteriosus using Amplatzer duct occluder - Mulyadi M. Djer; Bambang Madiyono (Indonesian Pediatric Society Publishing House, 2009)
Background  Transcatheter closure using amplatzer  duct  occluder (ADO)  is  currently the  treatment  of  choice for  patent  ductus arteriosus (PDA).  The  ADO  device  is  constructed from a Nitinol wire mesh containing 55% nickel. Up  to  now, there  is  still a controversy about the effects  of  nickel contained in ADO. Objectives  To  determine blood nickel level  at  six months after transcatheter closure  of  PDA  using  ADO,  toxic effects  of  nickel at six months after  PDA  closure using  ADO,  and the effects  of nickel  on  complete blood  count  (CBC), blood glucose and renal function. Methods  Subjects  were  patients  with  PDA  at  Integrated Cardiovascular Services,  Dr.  Cipto Mangunkusumo Hospital, Jakarta. Routine blood test and blood nickel levels were measured at  the time  of  the procedure,  and  at  the  end  of  the first, third,  and sixth months after intervention. Results  There  were  29  patients who underwent heart catheteri- zation  and  PDA closure using  ADO.  A time series analysis was conducted  on  23  patients who completed six-month follow-up after the intervention. Median blood nickel level before procedure was 58 ng/mL while  at  one, three  and  six months afterwards were 60, 63 and 64 ng/mL respectively.  The  blood nickel levels did not  differ significantly between pre- and  post-ADO. After  PDA closure,  no  toxic effects  of  nickel were found,  both  clinically and laboratorically. Conclusions  PDA  closure using  ADO  has no effects  on  the nickel levels, CBC, blood glucose and renal function;